Penicillium and patulin distribution in pears contaminated with Penicillium expansum. Determination of patulin in pears by UHPLC-MS/MS - Dong-mei WEI; Jun XU; Feng-shou DONG; Xin-gang LIU; Xiao-hu WU; Yong-quan ZHENG (Journal of Integrative Agriculture, 2017)
The danger of mycotoxin contamination entering the food supply through post-harvest infection is of perennial concern to food safety experts. To explore the distribution of Penicillium expansum and diffusion of its mycotoxin, patulin, in blue mold-damaged pears, Pyrus bretschneideri Rehd. cv. Yali obtained from markets and orchards in China were artificially inoculated with P. expansum and assayed for patulin accumulation and degree of fungal colonization. The inoculated pears were incubated until the lesions were 5, 10, 20, or 30 mm in diameter. We sampled tissue at a range of distances from the lesion, measured the spread of Penicillium by plate colony-counting methods, and used UHPLC-MS/MS to detect and quantify the patulin concentration. More P. expansum colony-forming units were isolated from pears with a higher degree of decay. Farther from the lesion, the fewer P. expansum colonies were observed, and the lower the patulin content detected. We found a significant difference in the patulin content between samples due to lesion size, and also in tissue sampled 10 mm away from the lesion. In consideration of this finding, to ensure food safety, we recommend that when a blue mold rot lesion on pear is 5, 10, or 20 mm in diameter, 20, 30, and 40 mm beyond the lesion should be removed, respectively. If a lesion surpasses 30 mm in diameter, the whole pear should be thrown away.